Using Economic Diaries in an Ethnographic Study: What They Can Tell About the Financial and Daily Lives of Male and Female Sex Workers in Mombasa. (July 2022) - Igonya, Emmy Kageha; Nencel, Lorraine; Sabelis, Ida; Kimemia, Grace
This article has two objectives: first, to contribute to the academic understanding of the relationship of money with sex work by going beyond purely instrumentalist conceptualizations; and second, to inform interventions aiming to empower sex workers' economically. Qualitative research was conducted to better understand the financial lives of sex workers in Mombasa, Kenya. The article draws largely on a participatory method using 12 economic diaries accompanied by 30 informal discussions. We complement the economic diaries with 24 in-depth interviews, key informant interviews and participant observations conducted between 2014 and 2017. We found that sex workers' savings, spending, and earning practices were highly influenced by stigma, mobility and economic insecurity. We also found that sex workers gave substantial meaning to the idea of 'quick money', which reflected their daily financial strategies. The likelihood for development interventions to succeed will increase when sex workers are directly involved and not just recipients in programmes; furthermore, that programmes adequately recognize and address the needs and desires of sex workers and understand the socio-economic dynamics shaping sex work. In this article, these socio-economic factors revealed through the process and method of participants' writing economic diaries.